Pendampingan dan Pemberdayaan Lembaga Masyarakat Desa Hutan (LMDH) Mekarmukti melalui Metode Asset Based Community Development - Saripudin, Udin; Madjakusumah, Deden Gandana; Handri, Handri; Ihwanudin, Nandang; Nurrachmi, Intan; Efendi, Nur; Yuristama, Agus Prakarsa; Hoerurohman, Aditya (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The Mekarmukti Forest Village Community Institute (LMDH) is a farmer organization established to implement the Community Forest Management (PHBM) partnership program with Perhutani in Mekarwangi Village, Ibun District, Bandung Regency. LMDH Mekarmukti comprises five Forest Farmers Groups (KTH) with approximately 280 members, cultivating 100 hectares of Perhutani land, primarily focused on Arabica coffee plants. Like many rural communities, LMDH Mekarmukti faces various challenges. One major obstacle for its members is limited market access and the inability to add value to their coffee products, resulting in selling coffee logs to middlemen. This significantly reduces their income and impacts their welfare. Hence, it is crucial to provide assistance and empower the community by raising awareness about their assets and improving their welfare. The empowerment approach used is the ABCD (Asset-Based Community Development) method, which involves identifying assets, planning and evaluating programs to enhance farmers' progress and welfare. By employing the ABCD method, the aim is to increase awareness and optimize asset utilization. The successful implementation of the ABCD method requires collaboration among farmers, the community, and the government to jointly support farmer empowerment programs and improve their welfare.